2009
DOI: 10.1021/nn8008728
|View full text |Cite
|
Sign up to set email alerts
|

Size-Selective Diffusion in Nanoporous but Flexible Membranes for Glucose Sensors

Abstract: A series of nanoporous membranes prepared from polyethylene-block-polystyrene were applied for size-selective diffusion of glucose and albumin molecules. Millimeter-sized test cells for characterization of such molecular diffusions were designed assuming an implantable glucose sensor. The prepared nanoporous membrane exhibits excellent flexibility and toughness compared to conventional nanoporous membranes of brittle alumina. Pore size of the membranes could be controlled from 5 to 30 nm by varying preparation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
106
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(108 citation statements)
references
References 54 publications
(65 reference statements)
2
106
0
Order By: Relevance
“…Other nanoporous polymeric systems such as polyimide [193], polyethylene [194], or polycarbonate (PC) [195] have also been investigated. Smuleac and coworkers [195] demonstrated that the MWCO of Na 2 SO 4 salt was higher in the membranes with lower pore sizes (a difference up to 800% for a feed concentration of 2 mM).…”
mentioning
confidence: 99%
“…Other nanoporous polymeric systems such as polyimide [193], polyethylene [194], or polycarbonate (PC) [195] have also been investigated. Smuleac and coworkers [195] demonstrated that the MWCO of Na 2 SO 4 salt was higher in the membranes with lower pore sizes (a difference up to 800% for a feed concentration of 2 mM).…”
mentioning
confidence: 99%
“…There have also been studies on thin membrane platforms containing free standing polymer membranes (17)(18)(19), inverse opals (20) as well as protein (21), and block copolymer membranes (22)(23)(24). To provide improved membrane robustness, allow miniaturization, as well as the possibility to integrate with other ionic and electronic devices, silicon-based platforms are the perfect choice.…”
mentioning
confidence: 99%
“…From these results, it comes out that the glucose diffusion coefficient in these membranes is only ∼5 times smaller than in water (D = 6.73 × 10 −4 mm 2 /s [16]). Considering the relative standard deviation of 23%, this value is of the same order of magnitude that the diffusion coefficient in a 20 nm asymmetric alumina membrane from Whatman (1.39 × 10 −4 mm 2 /s) and much higher than its value in nanoporous polyethylene membrane (0.18 × 10 −4 mm 2 /s) [2]. This quite high diffusivity is remarkable when considering all possible effects impeding diffusion in nanoporous membranes.…”
Section: Glucose Diffusionmentioning
confidence: 69%
“…On the other hand, nanoporous membranes can also be used to confine large sensing molecules provided they exhibit a well defined pore size distribution. Various types of nanoporous membranes have been investigated for biosensors applications, including polymeric membranes [2], micromachined silicon membranes [3] and anodic alumina membranes [4]. With their good structural stability and intrinsic biocompatibility, nanoporous alumina membranes are typically well suited for biosensor size-selective interface.…”
Section: Introductionmentioning
confidence: 99%